Rancang Bangun Aplikasi Pendataan Kendaraan Operasional Menggunakan Metode Prototipe - Astri Aprilia Pratiwi; Muhammad Iqbal (Bulletin of Information Technology (BIT), 2023)
PT. HM Sampoerna Tbk is a leading tobacco company in Indonesia as well as an affiliate of the world's leading tobacco company, Philip Morris International, which has many operational vehicles to support the process of distributing their products but the process of managing operational vehicles for maintenance or repair is still not optimal. Operational vehicles that are poorly maintained can cause problems with the vehicle at any time, causing large losses for the company. Operational vehicle maintenance must be carried out regularly so that the company's operational activities are not disrupted and to keep the vehicle in good condition and primed for traveling to distribute the company's products. The author develops an operational vehicle data collection application using the prototype method, namely rapid software development to present an overview of existing ideas and problems and then obtain feedback from users so that prototypes can be repaired immediately. The application design uses DFD and ERD and the results obtained from this research are applications that can provide information about the history of operational vehicle repairs, remind operational vehicle data management staff to carry out periodic maintenance.